Parallelizing CPTEC' s General Circulation Model - Tamaoki, Jonas N.; Bonatti, José Paulo; Panetta, Jairo; Tomita, Simone (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1999)
We describe the first parallel version or CPTEC's General Circulation Model, targeting a 4 processor, shared memory NEC SX4. This paper emphasizes techniques to parallelize vintage production code, keeping results reproducible. Measured speed-ups compare favorably with Amdahl's Law predicted values.